Антология выдающихся достижений в науке и технике. Часть 9: Создание квантовых генераторов электромагнитного излучения сверхвысокой частоты - Баранов, М.И. (Електротехніка і електромеханіка, 2012)
A brief scientific and historical essay on the history of creation
of masers and maser amplifiers widely applied in various fields
of science and technology is given.